Health and safety ergonomic: Personal Protective Exosuits (PPE) / Ahmad Avizmuqri Mohd Shamsul and Suryani Ahmad - Mohd Shamsul, Ahmad Avizmuqri; Ahmad, Suryani (2023)
Musculoskeletal diseases (MSDs) are a major problem in many sectors, impacting employees’ health and productivity globally. This research investigates the possibility of Personal Protective Exosuits as a novel approach to preventing and managing MSDs in the workplace. The abstract emphasises the increasing need for effective treatments to address the increased prevalence of MSDs, as well as the limits of established approaches to address this issue. The paper emphasises the relevance of Personal Protective Equipment (PPE) in boosting worker ergonomic support, with a particular emphasis on exoskeleton technology. Exosuits, which are meant to increase employees’ strength and alleviate their physical strain during duties, have the potential to lessen the dangers associated with repetitive or heavy-duty operations. Furthermore, the abstract digs into the advantages of exoskeleton adoption, such as weight distribution and muscle fatigue reduction. Personal Protective Exosuits help to avoid MSDs and encourage a safer working environment by improving worker skills and lowering biomechanical stress. Furthermore, the study investigates the use of exoskeletons in the management of existing MSDs, allowing people with such disorders to continue working with less pain and suffering. This component emphasises a larger influence of PPE on employees’ well-being and retention.